2000
DOI: 10.1051/agro:2000114
|View full text |Cite
|
Sign up to set email alerts
|

Soil roughness and overland flow

Abstract: Soil surface roughness affects surface depression storage, water infiltration, overland flow velocity as well as overland flow organisation. This paper attempts to give an overview of our knowledge of the effects of roughness on surface runoff and to indicate areas where further research is most needed. The relationship between soil surface roughness and depression storage is relatively well understood. On the other hand, few studies exist on the relationship between roughness and the infiltration characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(139 citation statements)
references
References 88 publications
6
128
1
4
Order By: Relevance
“…Entretanto, em alguns casos, como nos tratamentos PC-0 e PC-2, pequena elevação no valor do índice de rugosidade ao acaso foi observada após a aplicação da primeira chuva simulada. Essa tendência também foi verificada por Eltz & Norton (1997) e Govers et al (2000), atribuindo-se esse fato à consolidação do solo pelo impacto das gotas de chuva e ao rearranjamento dos torrões e agregados do solo após terem sido umedecidos. Com a aplicação das chuvas, totalizando 420 mm de lâmina de água, distribuídas em sete eventos de precipitação pluvial, a evolução dos valores do RR apresentou grande variabilidade de acordo com o tipo de preparo e nível de cobertura.…”
Section: Resultsunclassified
“…Entretanto, em alguns casos, como nos tratamentos PC-0 e PC-2, pequena elevação no valor do índice de rugosidade ao acaso foi observada após a aplicação da primeira chuva simulada. Essa tendência também foi verificada por Eltz & Norton (1997) e Govers et al (2000), atribuindo-se esse fato à consolidação do solo pelo impacto das gotas de chuva e ao rearranjamento dos torrões e agregados do solo após terem sido umedecidos. Com a aplicação das chuvas, totalizando 420 mm de lâmina de água, distribuídas em sete eventos de precipitação pluvial, a evolução dos valores do RR apresentou grande variabilidade de acordo com o tipo de preparo e nível de cobertura.…”
Section: Resultsunclassified
“…With the advances in research on soil erosion processes, the interest in measurement and modeling of the surface microrelief has increased, especially for use in mathematical models of soil loss using the evolution of surface water retention during rainfall events (De Roo et al, 1995;Govers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The soil roughness is mainly characterized by two indexes: the roughness index RR (random roughness) (Allmaras et al, 1966;Currence & Lovely, 1970) and tortuosity index T (Boiffin, 1984), both related to capacity of surface water storage in the soil (Onstad, 1984;Govers et al, 2000;Kamphorst et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Steichen 1984, Góvers et al 2000 identified that runoff can be significantly lower over rough surfaces. The thickness of the undecomposed litter layer in the QM plot was recorded as being 1.2 cm; it can be assumed, therefore, that the large litter layer filled depressions in the soil which shortened the water-retention time, thus ensuring the rapid movement of water down slope.…”
Section: Relationship Between Vegetation and Runoffmentioning
confidence: 99%